Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis High Order Thinking Skill (HOTS) - Ade Fitria; Muhammad Wijaya; Muhammad Danial (Program Pasca Sarjana UNM, 2020)
This study is research development, which aims at developing LKPD (worksheets) based on HOTS on periodic table of elements material which is valid, practical, and effective to be used in training higher-order thinking skills. The development model used in this study refers to 4-D development model, which consists of defining stage (define), designing stage (design), development stage (develop), and dissemination stage (disseminate). The devices developed are LKPD based on HOTS. LKPD based on HOTS which is developed is then validated by two experts. After being validated, the devices are tested at SMAN 2 Enrekang in grade X MIPA 6 with 34 students. The results of the study reveal that the resulting LKPD is valid with mean score of validation is 3.73 which is in very valid category. The practical and effective criterion are also met, the practicality test includes, (1) the implementation of LKPD based on HOTS is in the mean M = 1.79 in category (1.5 ≤ M ≤ 2.0) meaning that the aspect and criteria being observed is in entirely implemented category, (2) the students gave positive response with 47.06% which is very positive, 51.52% gave positive response, and (3) the teacher gave very positive response with the mean score of 3.42 which is practical and no revision. The LKPD based on HOTS has met effective criteria with the following results (1) the students’ learning activity is in the average of 93 which is very active category, (2) the students’ learning result has met effective criteria which obtained the mean score of 58 with the criteria of high level thinking skill level according to Lewy (51-75) which is in good category. Therefore, the conclusion is the product of LKPD based on HOTS developed is valid, practical, and effective.